Exploring career development experiences among working spouses in dual-career family situations - Mohd Hamin, Norshila; Abd Rahim, Nur Aira (Human Resource Management Academic Research Society, 2019)
This paper discusses the career development experiences among working spouses in dual-career family (DCF) situation. The purpose of this research was to understand the experiences and contributing factors that made spouses chose to be in dual-career family situation, as well as their perceptions on the benefits and challenges of DCF on their career development. This research was conducted using an exploratory qualitative method. Findings indicate that being in a dual-career relationship impacts how working spouses made decisions regarding their family responsibilities and career priorities within the family unit. The experiences described by the participants reflect the salience of their family and work roles in parallel to one another, thus creating unique career development pathways. The findings also revealed the inseparable worlds of work and family experienced by DCF couples, including the challenges faced and how they coped with it in order to advance in their career development.